Investigation on Ficus carica and Punica granatum Extracts as Eco-Friendly Corrosion Inhibitors for C1018 Carbon Steel in Acidic and Marine Environments - Abdlmanam S. A. Elmaryami; Omar Nashed; Mahmoulah Y. Abdulraheem; Abdul Hamid Omran Saleh; Salah Mohamed Sallab; Garrett Arciete; Rahel G. Rahel (New Environmentally-Friendly Materials, 2026)
This study evaluates the corrosion behavior of carbon steel in acidic medium and seawater in the presence of natural plant extracts derived from pomegranate peels and fig leaves as environmentally friendly corrosion inhibitors. The weight loss technique was employed to determine the corrosion rate and inhibition efficiency after an immersion period of 624 h, in the absence and presence of different inhibitor concentrations ranging from 12.5 to 100 ppm. The results demonstrated that pomegranate peels and fig leaves extracts were ineffective in the acidic medium, as negative inhibition efficiency values were recorded, indicating an increase in the corrosion rate compared to the blank solution. In contrast, the extracts exhibited noticeable corrosion inhibition performance in seawater, where positive inhibition efficiency values were observed and improved with increasing inhibitor concentration. Fig leaves extract showed superior performance, achieving a maximum inhibition efficiency of approximately 27.47% at a concentration of 100 ppm. This improvement is mainly attributed to the adsorption of organic compounds present in the extracts onto the steel surface. resulting in the formation of a protective film that reduces metal dissolution in the marine environment. The findings of this study indicate that pomegranate peels and fig leaves extracts are ineffective under the studied conditions in acidic environments but demonstrate promising potential as eco-friendly inhibitors in marine or saline conditions. These results highlight the critical influence of the corrosive medium on inhibitor performance and support the use of natural plant extracts as sustainable alternatives to conventional chemical inhibitors of corrosion.